Internal Communication Patterns in Improving Employee Performance in Macro Planning: Pola Komunikasi Internal dalam Meningkatkan Kinerja Pegawai Bidang Perencanaan Makro - Fenelon Howay; Zulaikha Zulaikha; Dhimam Abror (Indonesian Journal of Innovation Multidisipliner Research, 2025)
This study aims to analyze the communication patterns applied in the Macro Planning Division of BAPPERIDA, West Papua Province to improve the effectiveness of internal communication. This study uses a descriptive qualitative approach that focuses on understanding employee behavior, perceptions, and motivations in the context of the organization. The subjects of the study consisted of employees in the Macro Planning Division of BAPPERIDA who were selected through purposive sampling based on their competencies and roles. Data collection was carried out through in-depth interviews, direct observation, and documentation studies. The results of the study indicate that internal communication in the Macro Planning Division of BAPPERIDA is running well, which is reflected in the improvement of work quality, punctuality, initiative, ability, and smooth interaction between leaders and staff. Employees have completed planning tasks, such as RKPD, RAP, and RPJMD, although there are some minor obstacles faced. Supporting factors for employee performance include discipline, understanding of tasks, and punctuality in completing work. In addition, the leadership communication approach that emphasizes good coordination and active problem-solving also facilitates task completion. This study concludes that effective communication is an important factor in achieving organizational success, with no significant obstacles found thanks to established internal communication practices. These findings underscore the importance of effective communication in optimizing organizational performance, increasing employee productivity, and creating more solid working relationships within the organization.